Effect of vitamin C supplementation on outcomes in patients with COVID-19: a systematic review and meta-analysis - Xu, Wenhao; Wang, Peng; Wan, Jun; Tan, Yaheng; Liu, Yuyang; Chen, Qiwen; Zheng, Yuxin; Yu, Xueying; Fan, Sitong; Jorge Luis, Cuyubamba Dominguez; Zhang, Yu (Frontiers in Nutrition, 2024)
We would like to submit the enclosed manuscript entitled "Effect of Vitamin C Supplementation on Outcomes in COVID-19 Patients: A Meta-Analysis of Randomized Clinical Trials", which we wish to be considered for publication in Frontiers in Nutrition. We confirm that none of the material in this manuscript has been published or is under consideration for publication elsewhere.The ongoing COVID-19 pandemic has presented significant challenges globally, with millions of cases and fatalities reported. In this context, the potential role of vitamin C as a therapeutic agent has garnered attention, given its immunomodulatory properties and previous use in treating infections. However, the results of clinical studies on the efficacy of vitamin C supplementation in COVID-19 patients have been inconsistent.Our meta-analysis found that vitamin C supplementation did not reduce in-hospital mortality rates or ICU stay durations in COVID-19 patients compared to standard care. These findings challenge earlier suggestions of a survival benefit associated with vitamin C use in COVID-19 patients and emphasize the need for ongoing research to clarify its role in treatment protocols. We believe that our study makes a valuable contribution to the existing literature on COVID-19 treatment strategies and provides important insights for healthcare providers and policymakers. The rigorous methodology, adherence to established guidelines, and comprehensive analysis of the available data strengthen the reliability and validity of our conclusions.Thank you for your time and consideration. We look forward to hearing from you regarding the status of our manuscript.